Sheet silicates: Micas - Fleet M E (London Geological Society, 2004)
Volume 3A of the second edition of Rock-forming minerals focuses on the micas. Here theMica sections have been greatly expanded. The text covers such aspects as crystal structure, crystal chemistry, chemical spectroscopy, stability and phase relations, r
Keywords: Mica